Parents raise their children and grandparents spoil their grandchildren? (Research, Society and Development, 2022)
In recent years in western countries, also in Spain, the intensive care of grandparents towards their grandchildren has increased. The woman has left the house and the man has not entered and this space has been occupied by the grandparents, mainly to take care of the minors. It seems that these infants have deficits in aspects such as: loss of sense of authority, vague limits and rules, confusion of roles, low self-esteem… In order to carry out the research, we present official quantitative data and also different interviews with people who know the subject. The choice of many parents to delegate their responsibility for the care and education of their children to their grandparents may have present and future detrimental consequences for minors.